ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN SURAT PERTANGGUNGJAWABAN KEUANGAN PADA PEMERINTAH KABUPATEN BOVEN DIGOEL - Nimrod Basna; Bonifasia Elitha Bharanti; Juliana Waromi (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2016)
This paper studied the effect of human resources, regional budgeting planning and delays of third parties financial reporting to regional letters of financial accountability postponement. The study was conducted in Government Work Units in Boven Digoel Regency. There were 23 Work Units which involved in the study. There were 97 respondents using purposive sampling technique. An empirical test was run using Multiple Regression Model to test research hypotheses. The study found that human resources and regional budgeting planning significantly impacted on the delays of letter of financial accountability in Boven Digoel Regency. In addition, the delays of third parties financial reporting were not supported to have impact on regional letters of financial accountability postponement in the Regency. Key words: Human Resources, Regional Budgeting Planning, Delays of third parties financial reporting